Effects of animal protein feedstuffs partially replacing fishmeal in the diet of Macrobrachium nipponense. (14th September 2022) - Zhou, Qun‐Lan; Xiong, Yiwei; Li, Peng; Saidyleigh, Momodou; Yang, Chang; Li, Jingyuan; Sun, Cunxin; Zheng, Xiaochuan; Liu, Bo; Jiang, Sufei; Fu, Hongtuo
Abstract: Animal protein feedstuffs, including poultry by‐product meal (PBM), spray‐dried porcine solubles (SPS), hydrolysed feather meal (HFM) and spray‐dried egg product (SEP), were used to replace 5% fish meal (FM) in the diet of Macrobrachium nipponense, respectively, to evaluate their effects on growth performance. A diet containing 25% FM was used as the control treatment. The various diets were fed to quadruplicate groups of prawns for 10 weeks. Results showed that there were no significant differences in survival, final body weight or weight gain among different treatments. The feed conversion ratio of the SPS group was significantly higher than that of the control group. The protein efficiency ratio was significantly higher in the SEP group than in the other groups. The feed intake of the SEP group was significantly lower than that of the control group. Animal protein feedstuffs significantly affected the composition of prawns' muscle, while slightly affecting the muscle amino acid profile. Moreover, animal protein feedstuffs significantly affected the haemolymph biochemical parameters and hepatopancreas lipase and α‐amylase activities. These four animal protein feedstuffs regulated the target of rapamycin (TOR) and activated transcription factor 4 (ATF4) expressions in the hepatopancreas and muscle. Meanwhile activating transcription factor 3 (ATF3) in muscle was significantly up‐regulated. Moreover, acetyl‐CoA carboxylase (ACC) and fatty acid synthase (FAS) in hepatopancreas were significantly down‐regulated in all treatments, while FAS was only down‐regulated in the HFM group. In general, animal protein feedstuffs in the present study are all good candidates to partially replace FM in the diet of M. nipponense . Moreover, SEP is the best one among these animal protein feedstuffs.